Effectiveness of the leaf of Guava, Turmeric, and Javanese ginger (GUMAVIT) capsules against diarrhea in rabbits - Shefani Eka Putri; Reni Septiyaningsih; Fathul Majid Abdullah; Setiawan, Muhammad Herfa; Tri Puji Rahayu (Jurnal Ilmu Peternakan Terapan, 2026)
Diarrhea is a serious health problem in rabbits that can reduce productivity and increase mortality risk, highlighting the need for safe, natural treatment alternatives. This study aimed to evaluate the effectiveness of GUMAVIT herbal capsule supplementation, containing guava leaf powder, turmeric, and Javanese ginger, in reducing diarrhea severity in rabbits. This is the first study to evaluate the combination of these three herbal ingredients in a specific capsule formulation (GUMAVIT) as a natural therapy for rabbit diarrhea. The research was conducted from month September to November 2024 using six local rabbits aged 1–3 months with an average body weight of 897.5±143.96 g, divided into two treatments: T0 (without GUMAVIT/chemical medication) and T1 (600 mg GUMAVIT supplementation). Supplementation was administered once daily for one day following diarrhea induction. Observed parameters included fecal color, fecal texture, defecation frequency, and overall body condition, and data were analyzed using an Independent T-Test. Results showed that GUMAVIT supplementation had no significant effect (P>0.05) on fecal color or texture but significantly affected (P<0.05) defecation frequency and body condition. Supplementation with 600 mg GUMAVIT effectively reduced defecation frequency and improved rabbits general condition, indicating its potential as a natural herbal alternative for diarrhea treatment.